Measles vaccination of young infants in China: A cost-effectiveness analysis. Issue 29 (15th June 2020) - Janusz, Cara Bess; Wagner, Abram L.; Masters, Nina B.; Ding, Yaxing; Zhang, Ying; Hutton, David W.; Boulton, Matthew L.
Abstract: Background: Although global progress in measles control has been realized, achieving elimination has proven difficult in many regions of the world. China has adopted a goal of measles elimination but recent outbreaks predominantly affecting children <8 months who are ineligible for vaccination and incompletely protected by maternal antibodies has impeded progress. We assess the cost-effectiveness of adding an initial measles vaccine dose in China to earlier than the currently recommended 8 months of age. Methods: We conducted a cost-utility analysis comparing the costs and health benefits associated with adding a measles vaccine dose to the routine schedule at 4, 5, 6 or 7 months compared to the current recommendation for the first dose at age 8 months. A decision analytic model was developed in Microsoft Excel, including five non-severe and two fatal health outcomes associated with measles infection. Model parameters were informed by the literature and surveillance data. Future costs and health benefits were discounted at 3%. Primary outcomes included costs, Quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER) over a lifetime time horizon. Results: Lowering the recommended age for initiating the measles vaccination series to address susceptibility in children <8 months provided incremental health gains compared to minimal costs at the individual-level. The ICER was most favorable ($232.70 per QALY gain) for administering an initial dose at 4 months of age due to fewer incremental program costs when shifting measles administration to an immunization visit already established under the Chinese vaccination program. Conclusion: We found potential beneficial health gains at a minimum cost associated with adding an earlier measles dose <8 months of age in China. Further investigation about disease transmission dynamics is required to more fully assess the tradeoffs of administering measles at a younger age to infants in China.